Variation in Intensity and Costs of Care by Payer and Race for Patients Dying of Cancer in Texas. Issue 7 (July 2015) - Guadagnolo, B. Ashleigh; Liao, Kai-Ping; Giordano, Sharon H.; Elting, Linda S.; Shih, Ya-Chen T.
<x xml:space="preserve">Abstract</x> Purpose: To investigate end-of-life care for Medicaid, Medicare, and dually eligible beneficiaries dying of cancer in Texas. Methods: We analyzed the Texas Cancer Registry (TCR)-Medicaid and TCR-Medicare linked databases' claims data for 69, 572 patients dying of cancer in Texas from 2000 to 2008. We conducted regression models in adjusted analyses of cancer-directed and acute care and total costs of care (in 2014 dollars) in the last 30 days of life. Results: Medicaid patients were more likely to receive chemotherapy and radiation therapy. Medicaid patients were more likely to have >1 emergency room (ER) [odds ratio (OR)=5.27; 95% confidence interval (CI), 4.76–5.84], and were less likely to enroll in hospice (OR=0.59; 95% CI, 0.55–0.63) than Medicare patients. Dual eligibles were more likely to have >1 ER visit than Medicare-only beneficiaries (OR=1.19; 95% CI, 1.07–1.33). Black and Hispanic patients were more likely to experience >1 ER visit and >1 hospitalization than whites. Costs were higher for nonwhite Medicare, Medicaid, and dually eligible patients compared with white Medicare enrollees. Conclusions: Variation in acute care utilization and costs by race and payer suggest efforts are needed to address palliative care coordination at the end of life for Medicaid and dually eligible beneficiaries and minority patients dying of cancer.